Evaluasi Pembelajaran dalam Keterampilan Berbicara pada Mata Pelajaran Bahasa Indonesia Siswa Kelas IV SDN Balaraja I - Ina Magdalena; Octaviani Dwi Crismaningrum; Nanda Chairunnisa; Na'imatul Jannah (RC-INSTITUT, 2020)
This study aims to describe (1) How to evaluate the learning of speaking skills in Indonesian language subjects in grade IV SDN Balaraja I (2) Barriers to teacher implementation of speaking skills evaluation in Indonesian language subjects in grade IV SDN Balaraja I and (3) Efforts teacher in overcoming obstacles in the implementation of the evaluation of speaking skills in Indonesian language subjects grade IV SDN Balaraja I. This study used a descriptive qualitative design, the subject of this study was the teacher grade IV. The object of this research is the way to implement speaking skills evaluation in Indonesian language subjects in grade IV SDN Balaraja I, the obstacles of teachers in the implementation of speaking skills evaluation in Indonesian subjects in class IV Balaraja I and the efforts of teachers in overcoming obstacles in the implementation of evaluation of speaking skills in subjects Indonesian language class IV students of SDN Balaraja I. Data collection in this study used observation and interview methods. Analysis of the data used is the Miles and Huberman analysis model. The results of this study indicate that (1) SDN Balaraja I in grade IV A students have several students who experience obstacles in speaking skills (2) there are three obstacles teachers in evaluating speaking skills, namely a) difficulties in preparing students' readiness to participate in learning, b) difficulty in arranging class hours, and c) difficulty in managing large classes, (3) and there are three attempts made by teachers in evaluating speaking skills a) implementing accurate strategies to motivate students, b) making time effective, and c) managing students' speaking time.